The importance of T cells of the innate immune system in the development of meta-inflammation of adipose tissue in obesity - A.E. Abaturov; A.А. Nikulina (Zaslavsky O.Yu., 2020)
This review of the scientific literature deals with the participation of αβT and γδT cells of the innate immune system in maintaining an anti-inflammatory environment in the physiological state of adipose tissue and their role in the development of meta-inflammation in obesity. Overweight due to an increase in adipose tissue is associated with the development of metabolic disorders, which not only significantly reduce the quality of life, but also have the risk of adverse cardiovascular events. According to modern concepts, the trigger of metabolic disorders is low-grade inflammation induced by adipocyte dysfunction in obesity. Metabolically active cells such as adipocytes in obesity secrete numerous anti-inflammatory cytokines and chemokines, which recruit various immune cells into adipose tissue or activate cells of the immune system, including T cells of the innate immune system. In obesity, mucosal-associated invariant T (MAIT) cells of adipose tissue express an overactivated phenotype and are characterized by unresponsiveness to signals of the TCR-associated pathway, significantly increasing in obese children than in children with physiological body weight. The data are presented on the importance of invariant natural killer T (iNKT) cells, which critically administer the functioning of Treg cells and macrophages in adipose tissue, activation of which causes not only the death of adipocytes, but also stimulates adipogenesis that promotes insulin-dependent glucose uptake by adipocytes, and, in turn, a decrease in the number of iNKT cells, which observed in obesity, leads to the development of meta-inflammation. Variable NKT cells excite plasmacytoid dendritic cells and induce a tolerogenic effect on conventional dendritic cells. The data are given that a decrease in the representation of γδT cells in adipose tissue in obesity determines the intensity of meta-inflammation and insulin resistance in experimental animals receiving a high-fat diet. In the near future, drug control of the activity of MAIT, NKT, and γδT cells may become one of the possible ways to suppress the activity of obesity-induced meta-inflammation and prevent the development of metabolic disorders.